THE EFFECT OF EXPERIENCE AND KNOWLEDGE ON FRAUD DETECTION WITH INTUITION AS INTERVENING VARIABLE - suhardi suhardi (JEM Jurnal Ekonomi dan Manajemen, 2018)
This study aims to examine the effect of the knowledge of government internal supervisors through the intuition of government internal supervisors to detect irregularities. The sample in this study was the auditor who served at the Regency and municipal Inspectorates in Bangka Belitung totaling 122 respondents. This study uses path analysis to examine the relationship between hypothesized variables. The results of the study concluded that the experience and knowledge of government internal supervisors had a significant effect on deviation detection. In addition to the knowledge of government internal supervisors through government intuition, internal supervisors influence the detection of irregularities. This research needs to be further developed, to get stronger empirical results, such as by adding other variables from deviation detection, further research can also expand the object of research, and use the experimental method.